Physiological indices of seven forage species in different tropical environments - Hernández, Erika Andrea; Duran Castro, Carlos Vicente; Silva Aguilar, Bernardo; Juárez Lagunes, Francisco Indalecio; Vélez Terranova, Oscar Mauricio; Mejía de Tafur, María Sara (Revista Mexicana de Ciencias Agrícolas, 2022)
Forages must constantly carry out adaptation processes to the different changes in environmental factors, which leads to their physiological variables being affected. The objective was to evaluate the physiological behavior of seven tropical forage species under different environmental conditions during 2019 in Palmira, Colombia. A randomized complete block design was implemented, in three locations with different altitudes, with four repetitions per species for a total of 28 experimental units per locality. A Lcpro+ portable photosynthetic measurement analyzer was used to collect data on the photosynthesis rate, stomatal conductance, transpiration rate and internal CO2. The data collected were analyzed using by means of a comparison of means with the Duncan test (p≤ 0.05). The physiological indicators of the species Estrella, Kikuyu and the legume Centrosema molle at the three altitudes and the two seasons would demonstrate the adaptation mechanisms that they develop in adverse places in which they settle.
Keywords: adaptability; altitude; forages; seasons